Tuberculosis Lymphoedema Cutis - Ramesh A; Sentamilselvi G; Begum Rehana; Janaki V R; Boopalraj J M (Wolters Kluwer Medknow Publications, 1998)
Two cases of tuberculosis cutis associated with hymphoedema are presented with clinical and histopathological features. Both the patients responded to the usual line of antituberculous therapy with the resolution of the lesions though the lymphoedema persisted.